Bone Marrow Involvement in a Dog with Cutaneous Mast Cell Tumor - Poggiani , Sabrina dos Santos Costa; Viana, Flávia Façanha; Branquinho, Rosana de Paula; Gama, Fernanda Gomes Velasque (Brazilian Journal of Veterinary Pathology, 2013)
Cutaneous mast cell tumors with bone marrow involvement are rarely described in dogs and are associated with a poor prognosis. The aim of this report is to describe a case of bone marrow involvement secondary to cutaneous mast cell tumor in a dog and to discuss clinical and pathological abnormalities associated to this finding. Clinical findings associated with bone marrow infiltration included anemia, thrombocytopenia, staging and recurrent and progressive disease. The dog showed a short survival time. A combination of clinical and laboratory evaluation helps in identifying dogs with this type of tumor with bone marrow involvement, since it is not a common metastatic site reported